2021
DOI: 10.37304/jem.v2i1.2657
|View full text |Cite
|
Sign up to set email alerts
|

Kinerja pegawai pada Biro Pengadaan Barang dan Jasa Sekretariat Daerah Provinsi Kalimatan Tengah

Abstract: Pengadaan barang dan jasa pemerintah merupakan salah satu penggerak penting dalam memacu pertumbuhan ekonomi baik di tingkat nasional maupun daerah. Pengadaan barang dan jasa pemerintah yang efisien dan efektif merupakan salah satu bagian yang penting dalam pencapaian kinerja dalam suatu organisasi. Kesuksesan suatu organisasi sangat ditentukan oleh kinerja, yang mana dalam artinya kinerja adalah melakukan suatu kegiatan dan penyempurnaan sesuai tanggung jawab dengan hasil yang diharapkan. Kinerja merupakan up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Performance can be defined as a description of the level of achievement of the implementation of a program in realizing the goals, objectives, mission, and vision of the organization contained in the strategic plan of an organization (Muabuay et al, 2021;Sulandari & Rihandoyo, 2014). This is in line with the understanding of employee performance, namely, the ability of employees to do something with specific skills (Adipratama & Husnatarina, 2021;Sumantri, 2015). Based on some of the understandings stated above, it can be concluded that the notion of performance is the result of specific work or activities carried out by individuals or groups to achieve programs or policies that have been prepared in an organization for a certain period of time.…”
Section: B Literature Reviewsupporting
confidence: 69%
“…Performance can be defined as a description of the level of achievement of the implementation of a program in realizing the goals, objectives, mission, and vision of the organization contained in the strategic plan of an organization (Muabuay et al, 2021;Sulandari & Rihandoyo, 2014). This is in line with the understanding of employee performance, namely, the ability of employees to do something with specific skills (Adipratama & Husnatarina, 2021;Sumantri, 2015). Based on some of the understandings stated above, it can be concluded that the notion of performance is the result of specific work or activities carried out by individuals or groups to achieve programs or policies that have been prepared in an organization for a certain period of time.…”
Section: B Literature Reviewsupporting
confidence: 69%